Health Condition of European Beech (Fagus sylvatica L.) According to Provenances in International Provenance Trial - Ćelepirović, Nevenka (Array, 2021)
The performance of European beech (Fagus sylvatica L.) is severely threatened by abiotic and biotic stresses, but the resilience of its provenances from distinct geographic areas has not been sufficiently studied. Therefore, the performance of European beech was investigated in an international provenance trial consisting of twenty-one natural populations originating from Central Europe and Southeast Europe located on Medvednica Mountain (Croatia). The performance of European beech was investigated by characterizing I) damage types, II) crown damage intensity, III) damage frequency, and IV) clustering of provenances based on damage types. Anthracnose, galls, chewing damages, and aphids were recorded on leaves, and canker on the trunk and branches. The crown damage intensity was minute (less than 10%) for all types of disease. Anthracnose was the most common damage, followed in descending order by galls, canker, chewing damages and aphids. When the types of damage were analysed using descriptive statistics (frequency analysis and clustering), significant differences were recorded between provenances (χ2=322.19, p